Rules to Identify Persons with Frailty in Administrative Health Databases*. Issue 4 (4th October 2017) - Urquhart, Robin; Giguere, Anik M.C.; Lawson, Beverley; Kendell, Cynthia; Holroyd-Leduc, Jayna M.; Puyat, Joseph H.; Kazanjian, Arminee; Straus, Sharon; Johnston, Grace M.
ABSTRACT: This study sought to develop frailty "identification rules" using population-based health administrative data that can be readily applied across jurisdictions for living and deceased persons. Three frailty identification rules were developed based on accepted definitions of frailty, markers of service utilization, and expert consultation, and were limited to variables within two common population-based administrative health databases: hospital discharge abstracts and physician claims data. These rules were used to identify persons with frailty from both decedent and living populations across five Canadian provinces. Participants included persons who had died and were aged 66 years or older at the time of death (British Columbia, Alberta, Ontario, Quebec, and Nova Scotia) and living persons 65 years or older (British Columbia, Alberta, Ontario, and Quebec). Descriptive statistics were computed for persons identified using each rule. The proportion of persons identified as frail ranged from 58.2-78.1 per cent (decedents) and 5.1-14.7 per cent (living persons). RÉSUMÉ: Cette étude avait pour objectif le développement de règles d'identification de la fragilité par l'utilisation de données administratives populationnelles sur la santé qui peuvent être appliquées dans différentes juridictions, en lien avec les personnes vivantes ou décédées. Trois règles d'identification de la fragilité ont été élaborées sur la base de définitions reconnues pour la fragilité, de marqueurs associés à l'utilisation de services, de la consultation d'experts. Ces règles ont été limitées aux variables retrouvées dans deux bases de données administratives communes en santé démographiques : les registres de congé des hôpitaux et les données sur les réclamations des médecins. Ces règles ont été utilisées pour identifier les personnes avec fragilité, qu'elles soient décédées ou en vie, dans cinq provinces canadiennes. Les données des participants provenaient de personnes décédées à l'âge de 66 ans ou plus (provinces : Colombie-Britannique, Alberta, Ontario, Québec, Nouvelle-Écosse) et de personnes vivantes âgées de 65 ans ou plus (provinces : Colombie-Britannique, Alberta, Ontario, Québec). Des statistiques descriptives ont été calculées pour ces personnes en utilisant chacune des règles. La proportion de personnes identifiées comme frêles se situait entre 58, 2 et 78, 1 % chez les personnes décédées, et entre 5, 1 à 14, 7 % chez les personnes en vie.